1985
DOI: 10.1016/0014-5793(85)80169-1
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP‐dependent phosphorylation of a 16 kDa protein in a plasma membrane‐enriched fraction of rat aortic myocytes

Abstract: Phosphorylation induced by carp-dependent protein kinase was examined in a plasma membrane-enriched fraction from control and P-adrenergic-stimulated rat aortic myocytes. Phosphorylation of a 16 kDa protein which copurified with the plasma membrane marker (Nab + Kc)-ATPase was most prominent. It was decreased by pretreatment of the myocytes with isoproterenol and the effect of isoproterenol was inhibited by propranolol. Both phosphorylation induced by CAMP-dependent protein kinase and its inhibition by isoprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In intact skeletal muscle, addition of insulin can mimick tumour-promoting phorbol esters in increasing both protein kinase C activity (Walaas et al, 1987) and phospholemman phosphorylation (Walaas et al, 1991). Other studies have shown that phospholemman is phosphorylated following activation ofaor ,8-adrenergic receptors in myocardial sarcolemma and after activation of /)-adrenergic or vasopressin receptors in smooth muscle (Jones et al 1979(Jones et al , 1980(Jones et al , 1981Manalan and Jones, 1982;Boulanger-Saunier et al, 1985;Presti et al, 1985;Boulanger-Saunier and Stoclet, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…In intact skeletal muscle, addition of insulin can mimick tumour-promoting phorbol esters in increasing both protein kinase C activity (Walaas et al, 1987) and phospholemman phosphorylation (Walaas et al, 1991). Other studies have shown that phospholemman is phosphorylated following activation ofaor ,8-adrenergic receptors in myocardial sarcolemma and after activation of /)-adrenergic or vasopressin receptors in smooth muscle (Jones et al 1979(Jones et al , 1980(Jones et al , 1981Manalan and Jones, 1982;Boulanger-Saunier et al, 1985;Presti et al, 1985;Boulanger-Saunier and Stoclet, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…PLM is a plasma membrane protein found in cardiac (6,41,43), skeletal (55,56), and smooth muscle (10), liver (13), and adrenal tumor cells (57). Activation of ␣-or ␤-adrenergic receptors in the myocardial sarcolemma results in increased phosphorylation of PLM (23,32,43); activation of ␤-adrenergic or vasopressin receptors in smooth muscle also increases phosphorylation (9,10). In isolated guinea pig heart, administration of the ␤-adrenergic agonist, isoproterenol, results in phosphorylation of PLM, coinciding with an increase in contractility (42).…”
mentioning
confidence: 99%
“…2). These data suggest that the 16/17-kDa phosphoprotein identified in smooth muscle plasma membrane preparations [12,13,14] was likely PLM. We found that the CP68 PLM signal correlated with cAMP-, but not cGMP-mediated relaxation (fig.…”
Section: Discussionmentioning
confidence: 86%
“…Three papers describe a 16- to 17-kDa phosphoprotein in smooth muscle that may well have been PLM (PLM has an apparent molecular weight of approximately 16 kDa on SDS gels) [1]. In 1985, Boulanger-Saunier et al [12] identified a 16-kDa phosphoprotein in a plasma membrane-enriched fraction of rat aortic smooth muscle cell membranes. This protein copurified with Na,K-ATPase and was phosphorylated by PKA in vitro and by isoproterenol in vivo.…”
Section: Introductionmentioning
confidence: 99%